2007
DOI: 10.1152/jn.01321.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Perception and Navigation in the Congenitally Blind

Abstract: Vestibular input is required for accurate locomotion in the dark, yet blind subjects' vestibular function is unexplored. Such investigation may also identify visually dependent aspects of vestibular function. We assessed vestibular function perceptually in six congenitally blind (and 12 sighted) subjects. Cupula deflection by a transient angular, horizontal acceleration generates a related vestibular nerve signal that declines exponentially with time constant approximately 4-7 s, which is prolonged to 15 s in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 63 publications
3
63
0
Order By: Relevance
“…Previous work on human linear and angular displacement perception found similar results to ours with a tendency to overshoot and undershoot certain displacements Ivanenko et al, 1997;Seemungal et al, 2007;Bergmann et al, 2011). An indication for the influence of prior experience can be found in work that shows that distance estimation and error magnitude vary considerably as a function of changes in the environmental experience (Ziemer et al, 2009) or stimulus range (Teghtsoonian and Teghtsoonian, 1978;Klatzky et al, 1990;Schwartz, 1999).…”
Section: Behavioral Findings In the Context Of The Literaturesupporting
confidence: 88%
See 1 more Smart Citation
“…Previous work on human linear and angular displacement perception found similar results to ours with a tendency to overshoot and undershoot certain displacements Ivanenko et al, 1997;Seemungal et al, 2007;Bergmann et al, 2011). An indication for the influence of prior experience can be found in work that shows that distance estimation and error magnitude vary considerably as a function of changes in the environmental experience (Ziemer et al, 2009) or stimulus range (Teghtsoonian and Teghtsoonian, 1978;Klatzky et al, 1990;Schwartz, 1999).…”
Section: Behavioral Findings In the Context Of The Literaturesupporting
confidence: 88%
“…Yet human path integration performance exhibits systematic errors. Characteristic overestimation and underestimation of traveled distances and turning angles and thus a tendency to bias toward certain displacements have been reported for path integration tasks in real and virtual environments Jürgens et al, 1999;Riecke et al, 2002;Seemungal et al, 2007;Glasauer et al, 2009b). Furthermore, systematic errors differ between studies: while participants correctly reproduced a 10 m distance in one study (Klatzky et al, 1990), they underestimated the same distance by 2 m in another one (Schwartz, 1999).…”
Section: Introductionmentioning
confidence: 88%
“…Given that the latter technique does not rely on eye movement recordings we investigated vestibular function in three groups, patients with congenital nystagmus, 9 severely reduced eye movements (chronic progressive external ophthalmoplegia, 11 ) and congenital blindness who have no structured eye movements. 12 On the basis of the measurement of the TC of the vestibulo-perceptual function we observed that in these patients perceptual TCs were shorter, that is, vestibulo-perceptual function was reduced. This somewhat suppressed vestibulo-perceptual function could be expected, given that long duration vestibular responses could create additional problems of disorientation in these patients when they move about in the environment.…”
Section: Basic Clinical Anatomy Of the Vormentioning
confidence: 89%
“…This is true when mapping spaces near and far from the body, for example, in manipulation and navigation, respectively. Both sighted and nonsighted people have shown such abilities using various sensory modalities (Kupers et al 2010;Seemungal et al 2007). It has been found that specific brain areas, including the hippocampus, posterior mesial lobe, and posterior parietal, occipital, and infero-temporal cortices, play an important role in spatial processing (Bird and Burgess 2008;Ekstrom et al 2003;Kravitz et al 2011;Latini-Corazzini et al 2010;Maguire et al 1998;Wascher et al 2009).…”
mentioning
confidence: 99%